Cross-cultural IP and communication symbols build cultural heritage brands a case study in China - Yubo, Shao; Jamal Rizal, Razali; Hasmadi, Hassan; Bo, Pan (Asian Scholars Network, 2025)
This study examines the promotional challenges faced by cultural heritage sites in China, including limited promotional methods, a disconnect with modern consumers' needs, and insufficient digital transformation. With the rise of new media, particularly short video platforms and social media, these issues present new opportunities for cultural heritage promotion. By integrating cross-cultural intellectual property and utilizing online communication strategies, cultural heritage sites can amplify traditional cultural symbols to enhance their appeal and competitiveness. Using Hongya Cave in Chongqing as a case study, this research explores how cultural heritage sites can transform into "internet-famous check-in spots" through communication semiotics. Hongya Cave, known for its unique stilted buildings and night-time lighting, gained online attention due to its resemblance to scenes from the Japanese film Spirited Away. Since 2016, Hongya Cave's journey from emergence to viral fame has been driven by cross-platform communication, including short video platforms like Douyin and Redbook, and social media such as Weibo and WeChat. User-generated content (UGC) reinforced cultural symbols such as “mystery” and “fairytale-like,” while traditional media reports consolidated its brand image, solidifying its status as a major tourist destination and city icon. This study highlights the significance of cross-cultural Intellectual Property (IP) integration and short video platforms in reshaping the image of cultural heritage sites. It also demonstrates the application of communication semiotics theory in constructing and spreading traditional cultural symbols, offering insights for the sustainable development and optimization of promotional strategies for cultural tourism.